Control of Wind Energy Conversion System and Power Quality Improvement in the Sub Rated Region Using Extremum Seeking - C. Ganesh; S. Anupama; M. B. Hemanth Kumar (IAES Indonesian Section, 2016)
For the purpose of better utilization and to have control over varying wind speeds we use variable speed wind turbines. The performance mainly depends on the system operating point. In this paper we implement extremum seeking (ES) which is a non-model based approach for maximum power extraction in the region between cut-in speed and rated speed. The convergence of the system depends mainly on the system dynamics so we go for non-linear control based on field oriented approach and also feedback linearization. For achieving maximum power at all wind speeds the outer loop of ES is used to tune the turbine speed in the sub rated region. By adjusting the voltage magnitude and electrical frequency through matrix converter we can achieve a fast transient response. The transient response can be improved by providing inner loop control based on field oriented control. Through this we can avoid magnetic saturation in the induction generator